Eksperimentalno preverjanje učinkov projektnega pouka pri predmetu spoznavanje okolja - Čagran, Branka; Sadek, Lidija; Ivanuš Grmek, Milena (Revija za elementarno izobraževanje, 2011)
Experimental Examination of the Effects of Project Teaching in the Subject Environmental Studies. In the first part of the article we define experiential and project teaching and point out its importance in teaching Environmental Studies in the first three years of primary school. In the second part of the article an empirical study is presented. We designed a didactic experiment including pupils from two third-grade classes. The experiment was conducted with respect to the following two thematic clusters in Environmental Studies: Me and Nature and What Can I Do?. Pupils were divided between an experimental and control group. We were interested in the effect of project teaching on pupils’ knowledge in Environmental Studies. The empirically obtained results show project teaching to have a significant positive influence on pupils’ knowledge in Environmental Studies because pupils from the experimental group were more successful at three levels of Bloom’s taxonomy for the cognitive domain (knowledge, understanding, application). We thus provided project teaching with the necessary, empirically verified basis for its further implementation in pedagogical practice.